Adjunctive dobutamine in patients with septic cardiomyopathy and tissue hypoperfusion: a blinded randomised controlled multicentre trial study protocol of the ADAPT-dobutamine trial - Bruno Giraudeau; Julie Léger; Philippe Vignon; Marine Goudelin; Bruno Evrard; Julien Vaidie; Samia Brit (BMJ Open)
Introduction Sepsis-induced left ventricular (LV) dysfunction participates in cardiovascular dysfunction and associated organ failure in patients with septic shock. The tested hypothesis is that dobutamine will reduce tissue hypoperfusion and secondary organ dysfunction in increasing oxygen delivery in fluid-filled patients with septic shock and associated symptomatic septic cardiomyopathy with documented low-flow state.Methods and analysis ADAPT–Dobutamine is a blinded, two parallel group, add-on, multicentre, randomised 1:1 and placebo-controlled trial. Patients will be included if hospitalised in the intensive care unit with septic shock (Sepsis-3 definition) and septic cardiomyopathy, identified using echocardiography (LV ejection fraction ≤40% and LV outflow tract velocity–time integral <14±1.5 cm). Non-inclusion criteria will include ventricular rate >130 bpm, severe ventricular arrhythmia, obstructive cardiomyopathy, severe aortic stenosis, ongoing acute coronary syndrome and indication for extracorporeal life support. Primary outcome will be the evolution of a modified Sequential Organ Failure Assessment score (excluding the neurologic system) during the initial intensive care unit stay encompassing screening (before randomisation), and from Day 1 to 3 after randomisation. Randomisation will be stratified on participating centres and previously documented heart failure (ejection fraction ≤40%). The use of open-labelled Dobutamine as a rescue therapy will be allowed in refractory shock based on strict clinical requirements. The use of alternative inotropes will not be allowed.Ethics and dissemination Approved by the Comité de Protection des Personnes Nord-Ouest IV from Lille (France) on 19 December 2019 (approval reference #19.04.05.36321). The results will be published in a peer-reviewed journal and presented in various congresses.Trial registration number NCT04166331.